TEACHER’ AND STUDENT’S ETHICAL CONCEPT IN AL GHAZALI'S PRESPECTIVE - Ma'rufi, Abdul Madjid (Journal Of Islamic Education And Pesantren, 2021)
The purpose of this study was to find out in depth al-Ghazali's concept of teachers and students. This research is library research. This study concludes several points. First, the ethical concept of teachers and students according to Al Ghazali is influenced by the insight of akhlaqi Sufism. Second, the implementation of the concept of teacher ethics according to Al Ghazali can be practiced by prioritizing the affairs of the hereafter, leaving something related to the world. But many concepts of teacher ethics and according to Al Ghazali can still be applied today in accordance with the concept of Indonesian teacher ethics. Although not all of them are carried out because the studies are different. The ethical concept of teachers and students offered by al-Ghazali is very important in the world of education in an effort to apply al-Ghazali's educational values in the midst of an increasingly modern society. Keywords: ethical concepts, teachers, students, moral education. KONSEP ETIKA GURU DAN PESERTA DIDIK PRESPEKTIF AL GHAZALI Abstrak Tujuan penelitian ini adalah untuk mengetahui secara mendalam konsep al-Ghazali tentang guru dan peserta didik. Penelitian ini adalah penelitian kepustakaan. Penelitian ini menyimpulkan beberapa poin. Pertama konsep etika guru dan peserta didik menurut Al Ghazali dipengaruhi oleh wawasan tasawuf akhlaqi. Kedua, Implementasi konsep etika guru menurut Al Ghazali dapat dipraktekkan dengan cara lebih mengutamakan urusan akhirat, meninggalkan sesuatu yang berhubungan dengan dunia. Tapi banyak konsep etika guru dan menurut Al Ghazali yang masih bisa diterapkan sekarang sesuai dengan konsep etika guru Indonesia. Walaupun tidak semua dilakasanakan karena memang kajiannya berbeda. Konsep etika Guru dan peserta didik yang ditawarkan al-Ghazali sangat penting dalam dunia pendidikan dalam upaya penerapan nilai-nilai pendidikan al-Ghazali di tengah-tengah masyarakat yang semakin modern ini. Kata kunci: konsep etika, guru, peserta didik, pendidikan moral .